2014
DOI: 10.3413/nukmed-0630-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland scintigraphy in Sjögren’s syndrome

Abstract: Visual analysis of salivary gland scintigraphy showed greater diagnostic utility than semiquantitative assessment in the diagnosis of SS, especially in the submandibular glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…Almost none of the studies that we found in the literature reported sensitivity, specificity, PPV, or NPV of SGS, except Kim et al [17], who found a sensitivity, specificity, PPV, and NPV of 88.2, 48.6, 65.1, and 79.1%, respectively. In that study, visual analysis was found to have a greater diagnostic utility than a semiquantitative assessment.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Almost none of the studies that we found in the literature reported sensitivity, specificity, PPV, or NPV of SGS, except Kim et al [17], who found a sensitivity, specificity, PPV, and NPV of 88.2, 48.6, 65.1, and 79.1%, respectively. In that study, visual analysis was found to have a greater diagnostic utility than a semiquantitative assessment.…”
Section: Discussioncontrasting
confidence: 57%
“…Traditional SGS focus on the qualitative measurement of delayed uptake or reduced concentration or reduced excretion after provocation with a salivary stimulating agent. In the past decades, several studies have evaluated semiquantitative parameters using different methods [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Although there is no consensus on the amount of tracer activity, data acquisition, or calculation of parameters, a quantitative evaluation of data seems to be more diagnostic than a qualitative interpretation of the dynamic scan [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a rheumatologist’s judgment, 54 patients (39.4%) were diagnosed as having SS, whereas the remaining 83 patients (44 with other autoimmune disorders and 39 with nonautoimmune sicca) were assigned to the non-SS group. Visual analysis revealed results similar to those of the study conducted by Kim et al [ 39 ]. Both studies revealed that uptake dysfunction was more frequent than excretory dysfunction in the SS group; these findings implicated that more profound disease severity of SS might exist in both studies while taking the phenomenon into consideration that the earliest and most common scintigraphic abnormality observed in SS is impairment of excretion, followed by a decrease in tracer accumulation [ 42 ].…”
Section: Comparing Quantitative With Visual Evaluationssupporting
confidence: 87%
“…In past decades, although a quite variety of studies verifying the utility of quantitative methods in interpreting salivary scintigraphy in patients with sicca have been published and been concisely listed [ 30 , 38 ], the use of quantitative indices remains insufficiently supported. Two studies have directly compared the diagnostic performance of visual and semiquantitative sialoscintigraphic analyses when doctors had a clinical suspicion that a patient had SS [ 39 , 40 ]. Kim et al assessed the sialoscintigraphic images of a total of 145 patients through a three-scale visual analysis and the quantitative indices as uptake ratio and percentage excretion.…”
Section: Comparing Quantitative With Visual Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation